Microplastic and Extracellular Vesicle Interactions: Recent Studies on Human Health and Environment Risks - Eleonora Calzoni; Nicolò Montegiove; Alessio Cesaretti; Agnese Bertoldi; Gaia Cusumano; Giovanni Gigliotti; Carla Emiliani (Biophysica)
Microplastics (MPs) are widespread environmental pollutants that have drawn significant attention due to their possible health risks to humans and animals, as well as their extensive presence in ecosystems. Recent growing evidence highlights a remarkable relationship between MPs and extracellular vesicles (EVs), nanoscale particles involved in intercellular communication. The purpose of this review was to investigate how the relationships between MPs and EVs can affect cellular functions and how this interaction could impact environmental conditions leading to broader ecological risks. The interaction patterns and bioactivity of both MPs and EVs are strongly influenced by biophysical characteristics such as hydrophobicity, surface charge, and particle size, which have received particular attention from the scientific community. Recent studies indicate that MPs affect EV distribution and their capacity to function appropriately in biological systems. Additionally, MPs can modify the molecular cargo of EVs, which may result in alterations of cell signaling pathways. Understanding the interactions between MPs and EVs could provide important opportunities to comprehend their potential effects on human health and environmental systems, especially when it comes to cancer development, endocrine, metabolic, and inflammatory disorders, and ecological disruptions. This review emphasizes the necessity of multidisciplinary research to clarify the molecular and biophysical mechanisms regulating the interaction between MPs and EVs.